THE MANGROVE ECOSYSTEM POTENTIAL FOR EDUCATIONAL TOUR DEVELOPMENT AROUND POND EDUCATION OF HASANUDDIN UNIVERSITY (UNHAS) IN MALLUSETASI DISTRICT, BARRU REGENCY. - Saru, Amran; Idrus, Rijal; Ilham, Muh. (Jurnal Ilmu Kelautan SPERMONDE, 2019)
This research was conducted in October 2017. The research location was the Hasanuddin University Education Pond, Bojo Village, Mallusetasi District, Barru Regency. The objectives of this study were: (a) To identify the various types of mangroves that make up the educational field in the Hasanuddin University Education Pond; (b) To Identify and to recognize the organisms associated with various types of mangroves that compose educational sites on the coast of the UNHAS Education Pond, and (c) To analyze data and information related to mangrove ecosystems and their associated organisms for the suitability of Education. Mangrove data collection using transect (Line transect) with 10 x 10 meters plot area, while collecting macrozoobenthos data using a scope and sieve net, while observing other parameters at the five stations with three replications carried out based on instructions (Englis, at.al., 1994; Noor, et al., 1999; Saru, 2013; and Bahar, et al., 2015). The results showed that 3 mangrove families were identified, namely Avicenniaceae, Rhizophoraceae, and Sonneratiaceae consisting of 7 species of mangrove, namely: Avicennia marina, Bruguiera gymnorhiza, Ceriops decandra, Rhizophora apiculata, R. mucronata, R. stylosa, and Soneratia alba. While the associated organisms, namely: 3 species for Carustacea, 4 species for Fish, 7 species for Mollusca, 3 species for Bird and 1 species for Reptile. Based on the results of land suitability analysis showed that the ecosystem of mangrove in Hasanuddin University Education Pond included in the conditional category for the development of Mangrove Education tour.